Dinâmica de preços e integração espacial dos mercados de arroz entre o Rio Grande do Sul e Santa Catarina (2000-2023) - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This study investigates the spatial integration and price dynamics between the rice markets of Rio Grande do Sul and Santa Catarina during the period from 2000 to 2023, theoretically grounded in market spatial integration theories and the Law of One Price. The econometric procedures employed included unit root testing with structural breaks, HEGY test, Granger causality test, Johansen cointegration test, and vector error correction model. Among the main findings, a structural break in August 2020 stands out. This break can be attributed to increased demand from industries to replenish their stocks at that time. Additionally, the results of the Vector Error Correction (VEC) Model indicated that the rice market is strongly integrated, as the long-term elasticity is approximately equal to one. Finally, it was concluded that the Law of One Price held true, supporting the idea that despite temporal variations and occasional shocks, prices tend to stabilize and converge to a single value in the long term, reflecting an efficient and integrated market
Price dynamics and spatial integration of rice markets between Rio Grande do Sul and Santa Catarina (2000-2023)
Keywords: Integração espacial; Cointegração; Mercado de arroz; Spatial integration; Cointegration; Rice market; CNPQ::CIENCIAS SOCIAIS APLICADAS